Effect of real time visual feedback on cardiologist's radiation exposure with an established electronic real time radiation system. Issue 7 (July 2016) - Gilligan, Paddy; Maguire, Susan; Fox, Elizabeth; McCann, Hugh; Sugrue, Declan; Foley, David; Casserly, Ivan; Doyle, Brendan
Abstract : Introduction: Real time visual feedback from electronic personal dosimeters has been shown to reduce occupational exposures when first introduced in an interventional cardiology setting[1] . In a recent paper by our group, we found that there was little difference one month and six months after the introduction of such a system. This study aims to assess the effect of removing the visual dose feedback on operator exposures. Materials and methods: Occupational collar exposures were monitored for cardiologists ( n = 5) over a series of mixed case types ( n = 95) in a busy interventional cardiology laboratory[1] . For half the cases the visual feedback screen was switched off during the procedure depending on an assigned random number. The radiation exposure data was analysed using a Mann Whitney U test. Results/discussion: There was no significant statistical difference in radiation exposure to the cardiologists between when the visual feedback system was switched off or on. Increased case numbers may point to differences between operators and case types. Conclusion: This study suggests that real time visual feedback may not prove beneficial to dose reduction in an established electronic monitoring system.